An achievement test in the television course on adventures in English - Navarro, Paz N. 1931- (1968)
This seminar paper is an achievement test divided into two equivalent forms for the English television course, Adventures in English. It is purely objective, composed of 300 items, all of which are multiple choice questions and divided into three parts--phonology, vocabulary and grammar structure. The test was administered on an experimental run to 117 President Sergio Osmena, Sr High School students who had just completed the television course on April 4, 1968. It must be emphasized that all the findings in this paper are tentative till further verifications. It is hoped that this paper will be used as an aid not only in measuring student achievement in the television course but also in determining that relative amount of emphasis that should be given to the various units of the same course to check its validity.